2010
DOI: 10.1080/01431160903229192
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in fPAR estimation of grass canopies under different stress situations and differences in architecture

Abstract: The fraction of intercepted photosynthetic active radiation (fPAR) is a key variable used by the Monteith model to estimate the net primary productivity (NPP). This variable can be assessed by vegetation indices (VIs) derived from spectral remote sensing data but several factors usually affect their relationship. The objectives of this work were to analyse the fPAR dynamics and to describe the relationships between fPAR and several indices (normalized difference vegetation index (NDVI), optimized soil adjusted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 43 publications
1
20
0
2
Order By: Relevance
“…However, the vegetation species have significant influence on most VIs and hence limit their applications (Myneni and Williams 1994;Viña et al 2011). Regression results in Table 3 and Table 4 showed that FPAR of different crops were correlated differently with VIs, consistent with the studies by Cristiano et al (2010) and Viña and Gitelson (2005). This suggests that under the same atmospheric conditions different crop types with different canopy architectures might have the same FPAR but different LAI.…”
Section: Correlation Between Field-measured Fpar and Vissupporting
confidence: 89%
See 3 more Smart Citations
“…However, the vegetation species have significant influence on most VIs and hence limit their applications (Myneni and Williams 1994;Viña et al 2011). Regression results in Table 3 and Table 4 showed that FPAR of different crops were correlated differently with VIs, consistent with the studies by Cristiano et al (2010) and Viña and Gitelson (2005). This suggests that under the same atmospheric conditions different crop types with different canopy architectures might have the same FPAR but different LAI.…”
Section: Correlation Between Field-measured Fpar and Vissupporting
confidence: 89%
“…Different VIs have been used for estimation of FPAR, and an ideal VI should be sensitive to FPAR through the whole dynamic range. However, the relationships between most VIs and FPAR are not stable due to impacts from several external factors such as the illumination geometry (Epiphanio and Huete 1995;Ogutu and Dash 2013;Roujean and Breon 1995), canopy background reflectance (Goward and Huemmrich 1992;Huemmrich and Goward 1997), and canopy structure parameters (Asner and Wessman 1997;Cristiano et al 2010;Dong et al 2015;Goel and Qin 1994;Goward and Huemmrich 1992). The relationships are also significantly affected by the saturation effect (Di Bellat et al 2004;Ridao, Conde, and Minguez 1998;Viña and Gitelson 2005).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…It is very important to collect reliable ground measured FPAR data for product validation and even for its utilization in modeling communities [46]. At present, a few instruments have been widely used, such as the Decagon AccuPAR ceptometer [15,23], tracing architecture and radiation of canopies (TRAC) [20], LI-191SA line quantum sensors or LI-190SZ (LI-COR Inc., Lincoln, NE, USA) [47,48], TM Cava devices line quantum sensor [49] and SKYE PAR quantum sensors (SKP 215 and SKR 110) [21]. Serbin et al [19] found MODIS C5 FPAR product follows well the temporal evolution of LAI-191SA FPAR data.…”
Section: Discussionmentioning
confidence: 99%